2005
DOI: 10.1177/073168405045022
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Elasto-plastic Stresses in the Composite Laminate with a Circular Hole Subjected to In-plane Loads by Means of Finite Element Method

Abstract: In this study, the analysis of the elastic and elasto-plastic stresses on the cross section of a composite laminate with circular hole subjected to in-plane loads is performed. The laminate with a circular hole is subjected to a uniform axial planar load along one edge where no load is exerted along the hole edge. Aluminum metal-matrix composite laminate is composed of four orthotropic plates oriented with different angles in the symmetric and anti-symmetric manner. The elastic and elastoplastic stresses are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Little attention has been devoted to FMLs containing a notch. [21][22][23][24] Khatibi and Ye 21 presented effective crack growth model to investigate the residual strength for various ARALL laminates containing circular hole. Wu et al 22 have studied the strength of Glare 4 with a circular hole and reported the delamination pattern and failure modes around the notch.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Little attention has been devoted to FMLs containing a notch. [21][22][23][24] Khatibi and Ye 21 presented effective crack growth model to investigate the residual strength for various ARALL laminates containing circular hole. Wu et al 22 have studied the strength of Glare 4 with a circular hole and reported the delamination pattern and failure modes around the notch.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors used finite element method to analyze elastic-plastic response and expansion of plastic zone in metallic layers of various FMLs. 23,24 The literature survey reveals that most of research works on FMLs containing a hole are limited to numerical modeling of structures with circular notch. In the present study, the blunt notch behavior of glass fiber reinforced aluminum with elliptic, circular and square notches has been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation